1994
DOI: 10.1164/ajrccm.150.5.7952554
|View full text |Cite
|
Sign up to set email alerts
|

Subjective and objective assessment of uvulopalatopharyngoplasty for treatment of snoring and obstructive sleep apnea.

Abstract: This study was designed to assess the subjective and objective effects of uvulopalatopharyngoplasty (UPPP) for treatment of snoring. We mailed a questionnaire dealing with snoring, quality of sleep, and interference with bed-partner's sleep to 100 unselected patients who were referred because of snoring. Replies were received from 69 patients. The answers were analyzed, and the subjective impressions were compared with preoperative and postoperative objective measurements of snoring and apnea. The average (+/-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
53
1
2

Year Published

1996
1996
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(62 citation statements)
references
References 13 publications
6
53
1
2
Order By: Relevance
“…Other studies have found differences between subjective and objective measurements of snoring, for example post uvulopalatopharyngoplasty where subjective improvement without objective alteration in snoring index was noted [11]. Furthermore, where objective improvements are noted, the correlation with subjective measures may be weak [12].…”
Section: Discussionmentioning
confidence: 97%
“…Other studies have found differences between subjective and objective measurements of snoring, for example post uvulopalatopharyngoplasty where subjective improvement without objective alteration in snoring index was noted [11]. Furthermore, where objective improvements are noted, the correlation with subjective measures may be weak [12].…”
Section: Discussionmentioning
confidence: 97%
“…Although snoring is a hallmark symptom of OSA, it is rarely measured objectively, and there is no standard method to do so. In this study, snoring intensity was objectively measured with an audiometer placed 1 m from the mouth, a technique similar to that used by previous groups [28,29]. Analysis was performed using the maximum for NREM and REM stages of sleep, with the area under the curve and the % sleep time >50 dB; therefore, the recordings are believed to be accurate.…”
Section: Discussionmentioning
confidence: 99%
“…Because they were restudied after a period with the device, and acted as their own controls, we are confident that this is a real effect. Although in surgical series the subjective improvement in snoring is hard to verify objectively [11,21], this has not proved to be the case with these devices. It must be acknowledged that this group of patients was largely self-selected by their continued use of the device, compared to those who had abandoned such a device and were not therefore eligible for the trial.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the above studies have looked at the occurrence of apnoeas and have not objectively measured the effect on snoring. Recent studies on the control of snoring by surgical techniques have suggested that the subjective reporting of improvement in snoring following interventions is unreliable and not confirmed by objective recordings [11]. In addition the reporting of snoring is unreliable in epidemiological studies [12].…”
mentioning
confidence: 99%